Perencanaan dan penghitungan pengolahan limbah tahu di Pabrik Tahu Banggle, Jombang - Palevi, Muhammad Raynaldi Reza; Noerhayati, Eko; Rahmawati, Anita (Jurnal Inovasi Pangan dan Gizi, 2024)
Background: The soybean processing industry into tofu has environmental impacts. This industry generates waste in the form of wastewater, which if discharged without prior management will cause damage and pollution to the environment. One of them is the Banggle tofu factory in Jombang. This study aims to create a plan and calculation of wastewater treatment installations at the factory. Methods: The research method is laboratory testing to determine the quantity of wastewater and direct observation to determine field conditions so that appropriate plans can be made according to the field conditions. Finding: This study found that the largest wastewater discharge is 18,000 L/day or 18 m3/day. Therefore, pipes are buried underground to avoid leakage. This research also produces the sizes that must be met by the wastewater treatment tank as a result of calculations. Conclusion: These sizes need to be considered in the installation of wastewater treatment facilities.